2011
DOI: 10.1210/jc.2010-1048
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Incidentaloma: An Endocrine Society Clinical Practice Guideline

Abstract: Practice guidelines for the endocrine evaluation and treatment of pituitary incidentalomas are presented, including indications for surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
388
1
24

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 488 publications
(417 citation statements)
references
References 48 publications
4
388
1
24
Order By: Relevance
“…Faced with a tumor remnant after incomplete surgical resection of NFPA, the current consensus guidance for practice is expectant follow-up and the use of radiotherapy or repeat surgery if required (1,29,30). This 'wait and see' strategy reflects the often unacceptable rate of longterm complications of radiation therapy as well as the usual indolent course of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Faced with a tumor remnant after incomplete surgical resection of NFPA, the current consensus guidance for practice is expectant follow-up and the use of radiotherapy or repeat surgery if required (1,29,30). This 'wait and see' strategy reflects the often unacceptable rate of longterm complications of radiation therapy as well as the usual indolent course of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the prevalence of pituitary abnormalities in the paediatric population undergoing neuroimaging for reasons other than pituitary disease is lacking and data are not available on pituitary incidentalomas (33). Indeed, previous studies have reported the prevalence of ES to be about 5-9% for all ages, with an increase in prevalence with age (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Except for pregnant and nursing women the maximum craniocaudal diameter should not be greater than 10 mm in sagittal cross-section images [50]. Since microadenomas may be endocrine disruptors, and macroadenomas can cause compression of the optic chiasm due to their size, further endocrinological and neuro-ophthalmological investigation should be performed (Category II) even in cases of low growth tendency [50]. c Axial FLAIR image of a 22-year old fMRI-volunteer.…”
Section: Pituitary Tumorsmentioning
confidence: 99%